STUDY THE EFFICACY OF ROHITAKMUL CHURNA IN THE MANAGEMENT OF SHWETAPRADAR W.S.R. TO LEUCORRHEOA - S. Bhalgat, *Madhuri; Kulthe, Mokshda (International Journal of Ayurveda and Pharma Research, 2018)
Every woman faces varies physiological and psychological changes during this "change of life" as a part of hormonal derangement. Now a days women’s health is of prime importance to get a healthy society. Woman play different roles in her life and these balances the family and keeps them nested together. It is important that she should remain healthy and proper attention should be paid towards her health. But because of their shyness and hesitation they would not discuss freely about their diseases relating to the exposable parts of the body and thus they get the diseases ultimately more and more complicated. Any deviation from natural process leads to complications like irritation in vagina due to excessive discharge which in turn causes divesting effect on marital harmony. This irritation can be caused due to infection or pathological manifestation in the vagina. “Shwetpradar” which is identified as white discharge which is commonest in all gynecological disorder’s like vaginitis. Leucorrhoea is a white discharge from the vagina. Normally, vaginal discharge occurs in regular variations of amount and consistency during the course of the menstrual cycle. A greater than usual amount is normal in pregnancy, and decrease is to be expected after delivery, during lactation, and after menopause. It may be physiological or pathological. Physiological excess of vaginal discharge does not require any treatment. But, the pathological conditions which necessitate treatment are those involving many infections due to Candida, Trichomonas, Gram negative, Gram positive etc. organisms. Whenever women suffer from certain pathological conditions the effective treatment is very essential. It is hoped that the research work in the field of Ayurveda will create much interest in the medical practice and for scientific application and interpretation of Ayurvedic formulations. Rohitakmul Churna is one above them. For this study we have use Rohitakmul Churna for treating Shweatpradar.